Endocrown em CAD-CAM : análise in vitro da carga máxima de fratura e do modo de falha - Slomp, Cilea (2015)
Objectives : To evaluate the maximum fracture load and the failure pattern of endodontically treated molars restored with endocrown by CAD-CAM system. Methods : Thirty healthy extracted molars were randomly assigned into 3 groups (n=10). After endodontic treatment, teeth were restored with endocrowns by CEREC/InLab (Sirona) system with three different materials: e.max CAD (Ivoclar Vivadent), Vita Mark II (VITA) or Lava Ultimate (3M ESPE). The specimens were subjected to the fractured resistance testing after 1,000,000 cyclic fatigue loading at 100N. Subsequently, they were tested in a universal testing machine with a crosshead speed of 1mm/min with compressive force to the long axis of the tooth. Results : According to a 2-way analysis of variance, the means of fracture resistence were (means followed by the same letter show no significant difference to ANOVA and Tukey) (p <0.05): Lava Ultimate 3048,6N ± 730.33 (A), e.max CAD 2188,5N ± 704.82 (B) and Vita Mark II 1129,5N ± 491.31 (C). Chi-square test (p = 0.0342) presented mostly restoration fractures to Vita Mark II (80%), statistically differing from the other groups. Fisher Exact test demonstrated predominantly reparable prognosis to Vita Mark II and unreparable to e.max CAD (p = 0.0029). Conclusion : Lava Ultimate showed the highest fracture resistance values, while Vita Mark II, the lowest. Vita Mark II group obtained predominantly reparable prognosis. In the other groups, the failure pattern was tooth + restoration with unfavorable prognosis to e.max CAD.